2013
DOI: 10.1155/2013/786409
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Dietary Patterns during Third Trimester in Association with Birthweight Characteristics and Early Infant Growth

Abstract: Our analysis examined the impact of maternal dietary patterns and lifestyle factors on markers of fetal growth, specifically birthweight and size for gestational age (small- (SGA) or large-for-gestational age (LGA)). The Infant Feeding Practices Study II, a prospective cohort study, surveyed pregnant women during their 3rd trimester, of which a subgroup (n = 893) completed a food frequency questionnaire. Maternal dietary patterns were evaluated by diet scores (Alternative Healthy Eating Index for Pregnancy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
132
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(138 citation statements)
references
References 30 publications
5
132
1
Order By: Relevance
“…When data from the Infant Feeding Practices Study II were used, no association was demonstrated between maternal diet during pregnancy and change in weight for length from 4 to 6 mo of age (14). Infant weight and length were collected from the motherÕs report from 2 Represents a high probability of consuming peaches, strawberries, canned fruits, broccoli, green beans or peas, corn, cabbage or coleslaw, white potatoes, sweet potatoes, refined grains, red and processed meats, pizza, french fries, sweets, salty snacks, and soft drinks.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…When data from the Infant Feeding Practices Study II were used, no association was demonstrated between maternal diet during pregnancy and change in weight for length from 4 to 6 mo of age (14). Infant weight and length were collected from the motherÕs report from 2 Represents a high probability of consuming peaches, strawberries, canned fruits, broccoli, green beans or peas, corn, cabbage or coleslaw, white potatoes, sweet potatoes, refined grains, red and processed meats, pizza, french fries, sweets, salty snacks, and soft drinks.…”
Section: Discussionmentioning
confidence: 98%
“…Only one other study, to our knowledge, has investigated the association between maternal dietary patterns during pregnancy and child growth trajectory (14). When data from the Infant Feeding Practices Study II were used, no association was demonstrated between maternal diet during pregnancy and change in weight for length from 4 to 6 mo of age (14).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…First, the cross-sectional design of the study does not allow for establishing causal relationships. Also, the FFQ previously validated for adults (20) was not developed for pregnancy; however, epidemiological studies have shown that FFQ can be used to measure nutritional dietary intake during pregnancy with acceptable validity and reproducibility (7,10) , including in Brazil (37) . Finally, the 0·018 0·471 − 0·031, 0·067 0·035 0·169 − 0·014, 0·084 0·033 0·180 − 0·015, 0·080 Family income ($US) † 0·0003 0·007 0·0001, 0·0005 0·0001 0·259 − 0·0001, 0·0003 − 0·0003 0·025 − 0·0005, 0·0003 Parity (n) − 0·083 0·041 − 0·163, −0·003 − 0·015 0·715 − 0·095, 0·065 0·142 <0·001 0·065, 0·219 Marital status 0·023 0·688 − 0·090, 0·136 0·002 0·977 − 0·111, 0·115 0·125 0·026 0·015, 0·236 Skin colour 0·015 0·761 − 0·084, 0·114 − 0·026 0·600 − 0·125, 0·072 0·021 0·678 − 0·077, 0·118 Adjusted Age (years) 0·021 0·058 − 0·001, 0·042 − 0·017 0·075 − 0·037, 0·003 − 0·018 0·061 − 0·037, 0·001 Schooling (years) 0·019 0·406 − 0·026, 0·065 0·025 0·132 − 0·018, 0·067 0·010 0·628 − 0·030, 0·050 Family income ($US) † 0·0006 0·011 0·0001, 0·001 0·0004 0·090 − 0·0001, 0·001 − 0·0004 0·102 − 0·001, 0·0001 Parity (n) − 0·097 0·030 − 0·184, −0·009 0·007 0·861 − 0·074, 0·089 0·098 0·012 0·021, 0·175 Marital status ‡ 0·030 0·588 − 0·078, 0·137 0·0004 0·993 − 0·100, 0·101 0·073 0·131 −0·022, 0·168 *The models were adjusted for total energy intake and pre-gestational BMI.…”
Section: Discussionmentioning
confidence: 99%
“…Early onset sepsis is presumably due to parental risk factors due to bacteria acquired before and during delivery and overall maternal genital tract as the main source of infection (5,6). Possible risk factors for EOS include low birth weight (LBW) (< 2500 grams) (7) or prematurity, maternal febrile due to bacterial infection during the two weeks before delivery, meconium stained liquor, prolonged rupture of membranes (PROM) for more than 18 hours and maternal chorioamnionitis or intraamniotic infection, which is defined as maternal leukocytosis (> 15000/mm), fever (> 38°C), uterine tenderness, tachycardia (> 100/min), fetal tachycardia (> 160/min) and purulent amniotic fluid (AF), prolonged labor, defined by more than 24 hours for each stage, and prenatal asphyxia (5,6). Late onset sepsis is related to bacteria acquired after delivery from nosocomial or community sources (5).…”
Section: Introductionmentioning
confidence: 99%